Pengaruh Program Majelis Taklim Dan Pendekatan Religius Terhadap Perilaku Keagamaan Masyarakat Di Majelis Taklim Walawrod Azzahro Lemah Abang, Kab. Bekasi, Jawa Barat - Khairunida, Daan Dini; Rosdiana Dewi, Eva (Marifah: Jurnal Pendidikan dan Pemikiran Peradaban Islam, 2025)
The taklim assembly, as a forum for Muslims to deepen religious teachings, plays a strategic role in fostering a profound understanding of Islam and cultivating a strong religious spirit. Beyond serving as a platform for religious education, the taklim assembly also contributes to shaping virtuous and ethical social behaviors, which are pivotal in navigating various societal changes. This research content to ascertain the effect of the Religious Program on Community Religious Behavior, the Influence of Religious Spirit on Community Religious Behavior, and the combined influence of the Taklim Assembly's Religious Program and Religious Spirit on Community Religious Behavior at the Taklim Walawrod Azzahro Lemahabang Assembly, Bekasi Regency, West Java. This study employs quantitative research methods at the Taklim Walawrod Azzahro Lemahabang assembly, with a population of 30. Data collection involves the use of questionnaire instruments and documentation, with the entire population serving as the sample. Data analysis utilizes multiple linear regression analysis through IBM SPSS 26, employing T-test (for partial hypothesis testing) and F-test (for simultaneous hypothesis testing) methods. Based on the data analysis, it is concluded that Religious Programs significantly influence Religious Behavior, with a T-count value of (2.919) exceeding the T-table value (2.052). Similarly, Religious Spirit significantly impacts Religious Behavior, with a T-count value of (3.465) surpassing the T-table value (2.052). Overall, both the Religious Program and Religious Spirit variables together exert a significant influence on Religious Behavior, as indicated by an F-count value of (52.743) against an F-table value of (3.354). In conclusion, the Religious Program conducted by the Taklim Council influences Community Religious Behavior, as does the Religious Spirit fostered within the Taklim Council. Together, the Religious Program and Religious Spirit of the Taklim Council shape Community Religious Behavior.